Seeing like a routier: Routiers’ borderscapes between Southern Europe and West Africa - Neto, P. F.; Falcão, R. (Etnográfica, 2023)
Routier is the self-designation employed by Senegalese men driving decades-old vehicles overloaded with mostly second-hand items from Southern Europe to be sold in West Africa. This activity involves navigating a constellation of overlapping politico-administrative, socio-economic, cultural and geographical borders. Building on the concept of borderscapes, whose plasticity and aesthetic qualities allows us to interrogate diverse border universes, this essay visually explores routiers border(ing) enactments and contingent meanings. By seeing like a routier, the piece seeks to feed an on-going debate not only on how to depict borders writ large but also on how certain groups of people embody, see and are seen by contemporary borders. **************************************************************************************************************************** Routier é como se autodenominam os indivíduos senegaleses que conduzem veículos com várias décadas de idade, do Sul da Europa para a África Ocidental. Os veículos viajam sobrecarregados com artigos de vária ordem, na sua maioria usados, que são vendidos, trocados e entregues ao longo do caminho. Esta atividade depende da navegação de uma constelação de fronteiras político-administrativas, socioeconómicas, culturais e geográficas, que se sobrepõem frequentemente. Partindo do conceito de borderscapes, cuja plasticidade e qualidades estéticas permitem interrogar diversos universos fronteiriços, este ensaio explora visualmente as representações e os significados das fronteiras para os routiers. Ao propor “ver como” um routier, interrogam-se as representações de uma multiplicidade de fronteiras, mas também sobre o modo como certos grupos de pessoas encarnam, veem e são vistos pelas fronteiras contemporâneas.